Quality of Clarias sp with the addition of ginger (Zingiber officinale) and turmeric (Curcuma longa) in cold storage - Akbar Fitriyanto; Nanik Suhartatik; Vivi Nur'aini; Harto Widodo (AGROINTEK, 2025)
Apart from being sold in whole form, fish is also sold in ready-to-use fillets. Fillets were easier for buyers because they were practical, easy to use, and clean. The disadvantage of serving in the form of fillets was that they were very susceptible to damage due to the ease of damage. Fish fillets have a high moisture and protein content. Without any protection, this material will quickly deteriorate. This study aimed to determine the effect of ginger and turmeric extracts on catfish fillets stored at cold temperatures The study used a factorial complete randomized design with the ratio of ginger and turmeric extracts as the first factor and storage days as the second factor. The results show that the use of ginger and turmeric as additional ingredients in the storage of catfish fillets was less effective in inhibiting fillet deterioration. The moisture content of the catfish fillets decreased from 82.66% to 70.51% after 6 days of cold storage. The pH value of the catfish fillet increased, while water-soluble protein and TVB-N were varied for some treatments. The pH value of fresh fish fillets without the addition of ginger and turmeric was 5.50 and reached 6.30 after 6 days of cold storage. Fillets with turmeric and ginger have a lower pH (6.15), and the ratio of the rhizome extracts did not significantly affect the pH value. According to the TVBN value, ginger and turmeric extracts could maintain the quality of fish fillets for up to 4 days at cold temperatures. Further research needs to be done to study the effect of packaging on the fresh fillet quality.